Stimulasi Multisensori sebagai Fondasi Pembentukan Karakter pada Anak Usia Dini - Mimin Sa’adah; Purwati Purwati (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Early childhood is recognized as the golden age, a critical period for establishing neurological foundations and character traits that influence subsequent stages of development. Multisensory stimulation, defined as structured stimulation of the tactile, vestibular, proprioceptive, visual, auditory, olfactory, and gustatory systems, is considered an important approach but has not yet been comprehensively explored. This article aims to synthesize research findings published between 2020 and 2026 regarding the relationship between sensory stimulation and character development in early childhood, including the values of discipline, independence, responsibility, self-confidence, cooperation, empathy, and emotional regulation. This study employed a literature review using a qualitative descriptive-analytical approach. The data were analyzed through content analysis and narrative synthesis. The findings indicate that well-structured sensory stimulation delivered through multisensory play activities enhances children's emotional regulation, independence, and social interaction. Furthermore, sensory stimulation functions as a neurological mediator for the internalization of character values within the framework of moral knowing, moral feeling, and moral action. It can be concluded that early childhood education curricula should systematically integrate evidence-based sensory stimulation. In addition, the competencies of teachers and parents need to be strengthened to create sensory-rich environments that are responsive to the unique developmental needs of each child